PERANCANGAN ISLAMIC BORARDING SCHOOL DENGAN KONSEP ARSITEKTUR MODERN DI KUNINGAN JAWA BARAT - Mela Sari Fatonah; Putri Suryandari; Sri Kurniasih (MAESTRO, 2022)
Islamic Boarding School is one type of Indonesian Islamic education that aims for students and their female students to carry out formal education according to their level which at the same time can explore Islamic religious knowledge by participating in daily activities in a school environment and residing in a dormitory or cottage. Boarding School is a school that has dormitories, where students live, total learning in the school environment. Therefore, all kinds of necessities of life and learning needs are provided by the school. Therefore, with the design of the Islamic Boarding School, it is hoped that it can trigger the enthusiasm of the younger generation to continue their education to a high level